Social capital on the basis of spectating sports - Mojtaba Rajabi; Mahdi Talebpour; Zahed Ghaderi; Hasan Assadi (Gonabad University of Medical Sciences, 2019)
As a determinant of social health, attention has been paid to social capital, and also to sport as one of the ways of developing and accelerating the development of social capital. The purpose of this study is to investigate the social capital from the volleyball nations league perspective of sport spectators. The research was a cross-sectional study carried out using random sampling on 456 volleyball nations league spectators. Gibson et al.'s questionnaire was used to collect the data. "Trust and security" had the highest meaning among the social capital aspects, There was no significant difference between men's and women's social capital. A significant difference was observed only in terms of the "trust and security" dimension between the social capital of single and married individuals. Furthermore, in terms of social relationships and individuals with a master's degree and higher, the different aspects of social capital based on education were significantly different than those holding a bachelor's degree. Sport contests can be regarded as one of the generators of social capital in society. In addition, authorities can improve the social capital of society by planning and creating suitable conditions for these people and by taking into account their demographic status.